Preparation method of unfired negative carbon geopolymer pottery and co-fired product with low-temperature glass glaze
Patent Information
- Application Number
- CN202611173480.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-04
- Publication Date
- 2026-10-16
AI Technical Summary
[0002]现有的陶瓷制品通常需经1000℃以上高温窑炉烧成,能耗高、碳排放量大,且生产周期长
本发明提供的免烧负碳地聚合物陶土及共烧工艺,无需传统陶瓷的1000℃以上高温烧结,大幅降低了生产能耗和碳排放。制品具有陶瓷质感和食品级表面,可广泛应用于日用陶瓷、工艺品、建筑装饰材料等领域。同时,配方中碳酸钙的引入实现了CO2的永久性碳封存,契合“双碳”目标,具有良好的产业应用前景和社会效益。
Smart Images

Figure CN122916607A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a non-fired negative carbon geopolymer clay and a method for preparing products co-fired with low-temperature glass glaze, and is applied in the field of inorganic non-metallic materials and environmentally friendly building / crafts technology. Background Technology
[0002] Existing ceramic products typically require firing in kilns at temperatures exceeding 1000℃, resulting in high energy consumption, significant carbon emissions, and long production cycles. Furthermore, the mining of traditional ceramic raw materials, such as clay, damages the environment, and the firing process also releases large amounts of CO2 and NO. x Emissions and environmental pressures are increasing.
[0003] However, existing non-fired materials have many defects. Commercially available non-fired clays mostly rely on organic molecular cross-linking agents or simple cement-based binders, resulting in the following problems: 1. Uncontrollable hardening speed: Some products set too quickly, making it impossible to shape them in time; some products dry slowly and do not harden for a long time; 2. Large drying shrinkage and easy cracking: Improper use of water-retaining agents or excessively high water-solid ratios lead to uneven water loss inside and outside, resulting in cracks; 3. Poor surface texture: The finished product has a texture similar to gypsum, lacking the glassy luster and cool touch of ceramics; 4. Poor wear resistance and water resistance: The surface is porous, easily absorbs water, and is easily scratched, making it unsuitable for tableware; 5. Unable to withstand subsequent glazing: The organic cross-linking system decomposes at high temperatures and cannot be co-fired with low-temperature glazes.
[0004] While existing geopolymer materials have the advantage of low-temperature curing, they rarely systematically introduce inorganic carbon sources such as calcium carbonate for permanent carbon sequestration, and lack co-firing processes that match low-temperature glass glazes. As a result, the products cannot achieve the three-in-one goal of "no-firing molding, negative carbon sequestration, and ceramic texture".
[0005] Therefore, it is necessary to study a new non-fired negative carbon geopolymer clay and its preparation method for co-firing with low-temperature glass glaze to overcome the above problems. Summary of the Invention
[0006] The purpose of this invention is to overcome the defects of the prior art and provide a non-fired, low-shrinkage, crack-resistant, carbon-negative polymer clay formula, as well as a matching process of co-firing the wet blank at 450°C with the low-temperature glass glaze, so that the product can obtain the texture of a real ceramic and the surface sealing function of a high-quality product without high-temperature kiln firing.
[0007] This invention is implemented as follows: This invention provides a non-fired negative carbon geopolymer clay, comprising the following components in parts by weight: 50-60 parts of metakaolin; 15-25 parts of negative carbon calcium carbonate; 10-20 parts of alumina micro powder; 5-15 parts quartz powder; 8-15 parts of anhydrous sodium metasilicate; 1-3 parts sodium fluorosilicate; 30-45 parts water.
[0008] Furthermore, the metakaolin contains at least 70% active Al2O3 and SiO2; the negative carbon calcium carbonate contains at least 90% CaCO3; the alumina micro powder is α-Al2O3 with a purity of at least 95%; and the quartz powder contains at least 99% SiO2.
[0009] Furthermore, the modulus of the anhydrous sodium metasilicate is 2.0-3.3.
[0010] Furthermore, the amount of sodium fluorosilicate used is 12%-15% of the amount of sodium metasilicate with zero water.
[0011] Furthermore, the ratio of the amount of water used to the total mass of the non-fired negative carbon polymer clay powder is (0.35-0.40):1.
[0012] Furthermore, the low-temperature glass glaze used in conjunction with the aforementioned non-fired negative carbon polymer clay comprises the following components in parts by weight: 6-7 parts low-temperature frit powder; 1.5-2 parts quartz powder; Kaolin 1-1.5 parts; Carboxymethyl cellulose 0.1-0.3 parts; Sodium tripolyphosphate 0.03-0.08 parts; Water 3-4 parts.
[0013] Furthermore, the initial melting point of the low-temperature frit powder is 400-420℃, and it is fully vitrified at 450℃.
[0014] This invention also provides a method for preparing a product co-fired with non-fired negative carbon geopolymer clay and low-temperature glass glaze, comprising the following steps: Dry powder premix: Mix metakaolin, calcium carbonate, alumina powder and quartz powder in proportion, and dry mix for 2-5 minutes until uniform to obtain a dry powder mixture; Liquid preparation: Sodium fluorosilicate is first dissolved in a portion of water, and then mixed and stirred with the remaining water and anhydrous sodium metasilicate to obtain a mixed liquid; Wet mixing: Pour the liquid mixture into the dry powder mixture and stir for 2-3 minutes until it becomes dough-like to obtain the dough; Compaction molding: The blank is filled into the mold, compacted and vibrated to remove bubbles, to obtain the blank; Low-temperature pre-drying: The green body is pre-dried in an oven at 50-70℃ for 12-24 hours to obtain a semi-dry green body; Glaze preparation: Dry mix low-temperature frit powder, quartz powder and kaolin, then pass through a sieve. Dissolve carboxymethyl cellulose and sodium tripolyphosphate in water and add to the mixture. Stir well and let stand to mature to obtain glaze. Glazing of wet blank: Apply the glaze slurry to the surface of the semi-dry blank, apply 2-3 layers, with a total thickness of 0.4-0.6 mm, and allow each layer to air dry for 10-12 minutes to obtain the glazed blank; Co-firing: The glazed body was co-fired according to the following temperature rise curve: The room temperature was raised to 120℃ at a rate of 1.8–2.2℃ / min, and the temperature was maintained for 15–25 min. Heating from 120℃ to 300℃ at a rate of 0.9–1℃ / min, and holding at that temperature for 30–40 min; Heating from 300℃ to 450℃ at a rate of 1.8–2.2℃ / min, and holding for 10–15 min; The temperature was reduced from 450℃ to 300℃ at a rate of 1.8–2.2℃ / min. Cool down from 300℃ to room temperature and allow to cool naturally.
[0015] Furthermore, in the co-firing step, the glazed body is co-fired according to the following temperature rise curve: Heat the room temperature to 120℃ at a rate of 2℃ / min and hold for 20min. Heat from 120℃ to 300℃ at a rate of 1℃ / min, and hold for 30–40 min. Heat from 300℃ to 450℃ at a rate of 2℃ / min, and hold for 10–15 min. Cooling from 450℃ to 300℃ at a rate of 2℃ / min; Cool down from 300℃ to room temperature and allow to cool naturally.
[0016] Furthermore, in the compaction molding step, the vibration degassing time is 10 to 15 seconds; after co-firing, the product is also wet-polished using 800 to 1500 grit sandpaper and then rinsed with water.
[0017] The present invention has the following beneficial effects: The non-fired negative carbon geopolymer clay and co-firing process provided by this invention eliminate the need for high-temperature sintering above 1000℃ required for traditional ceramics, significantly reducing production energy consumption and carbon emissions. The resulting products possess a ceramic texture and a food-grade surface, making them widely applicable in daily-use ceramics, handicrafts, and building decoration materials. Furthermore, the introduction of calcium carbonate into the formula achieves permanent CO2 carbon sequestration, aligning with the "dual carbon" goal and demonstrating promising industrial application prospects and social benefits. Attached Figure Description
[0018] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1 This is a schematic diagram of the co-firing heating curve provided in an embodiment of the present invention. Detailed Implementation
[0020] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] This invention provides a non-fired negative carbon geopolymer clay, comprising the following components in parts by weight: 50-60 parts of metakaolin; 15-25 parts of negative carbon calcium carbonate; 10-20 parts of alumina micro powder; 5-15 parts quartz powder; 8-15 parts of anhydrous sodium metasilicate; 1-3 parts sodium fluorosilicate; 30-45 parts water.
[0022] Furthermore, the metakaolin contains at least 70% active Al2O3 and SiO2, and has a fineness of 200 mesh; the negative carbon calcium carbonate contains at least 90% CaCO3, and has a fineness of 200 mesh; the alumina powder is α-Al2O3, with a purity of at least 95% and a fineness of 325 mesh; and the quartz powder contains at least 99% SiO2, and has a fineness of 200 mesh.
[0023] Furthermore, the modulus of the anhydrous sodium metasilicate is 2.0-3.3. The sodium fluorosilicate, as a hardening accelerator, is used at 12%-15% of the amount of the anhydrous sodium metasilicate. The ratio of the amount of water to the total mass of the non-fired negative carbon geopolymer clay powder is (0.35-0.40):1.
[0024] Furthermore, the low-temperature glass glaze used in conjunction with the aforementioned non-fired negative carbon polymer clay comprises the following components in parts by weight: 6-7 parts of low-temperature frit powder; Quartz powder 1.5-2 parts; Kaolin 1-1.5 parts; Carboxymethyl cellulose 0.1-0.3 parts; Sodium tripolyphosphate 0.03-0.08 parts; Water 3-4 parts.
[0025] Furthermore, the initial melting point of the low-temperature frit powder is 400-420℃, and it is fully vitrified at 450℃. It is also a lead-free and cadmium-free formulation. The low-temperature frit powder meets the heavy metal migration limits required by food contact material regulations, with lead migration ≤0.5mg / L and cadmium migration ≤0.25mg / L.
[0026] This invention also provides a method for preparing a product co-fired with non-fired negative carbon geopolymer clay and low-temperature glass glaze, comprising the following steps: Dry powder premix: Mix metakaolin, calcium carbonate, alumina powder and quartz powder in proportion, and dry mix for 2-5 minutes until uniform to obtain a dry powder mixture; Liquid preparation: Sodium fluorosilicate is first dissolved in a portion of water, and then mixed and stirred with the remaining water and anhydrous sodium metasilicate to obtain a mixed liquid; Wet mixing: Pour the liquid mixture into the dry powder mixture and stir for 2-3 minutes until it becomes dough-like to obtain the dough; Compaction molding: The blank is filled into the mold, compacted and vibrated to remove bubbles, to obtain the blank; Low-temperature pre-drying: The green body is pre-dried in an oven at 50-70℃ for 12-24 hours to obtain a semi-dry green body; wherein the vibration degassing time is 10-15 seconds.
[0027] Glaze preparation: Dry mix low-temperature frit powder, quartz powder, and kaolin, then pass through a 200-mesh sieve. Dissolve carboxymethyl cellulose and sodium tripolyphosphate in water and add to the mixture. Stir well and let stand to mature to obtain the glaze. Glazing of wet blank: The glaze slurry is applied to the surface of the semi-dry blank in 2-3 layers with a total thickness of 0.4-0.6 mm. Each layer is air-dried for 10-12 minutes at intervals to obtain a glazed blank. The glaze slurry is applied by spraying or brushing.
[0028] Co-firing: The glazed body is heated according to the following temperature curve (e.g.) Figure 1 (As shown) Co-fired: The room temperature was raised to 120℃ at a rate of 1.8–2.2℃ / min, and the temperature was maintained for 15–25 min. Heat from 120℃ to 300℃ at a rate of 0.9 to 1℃ / min and hold for 30 to 40 minutes. During this process, the heating rate must not exceed 1℃ / min, otherwise the internal air will break through the glaze and cause bubbles.
[0029] Heating from 300℃ to 450℃ at a rate of 1.8–2.2℃ / min, and holding for 10–15 min; The temperature was reduced from 450℃ to 300℃ at a rate of 1.8–2.2℃ / min. Cool down from 300℃ to room temperature and allow to cool naturally.
[0030] In this preferred embodiment, during the co-firing step, the glazed green body is co-fired according to the following temperature rise curve: Heat the room temperature to 120℃ at a rate of 2℃ / min and hold for 20min. Heat from 120℃ to 300℃ at a rate of 1℃ / min, and hold for 30–40 min. Heat from 300℃ to 450℃ at a rate of 2℃ / min, and hold for 10–15 min. Cooling from 450℃ to 300℃ at a rate of 2℃ / min; Cool down from 300℃ to room temperature and allow to cool naturally.
[0031] After co-firing, the product is further polished by wet grinding using 800-1500 grit sandpaper and then rinsed with water.
[0032] The entire process takes approximately 6-7 hours (including heat preservation), and smaller parts can be compressed to 4-5 hours.
[0033] The following comparison is made through multiple specific embodiments: Example 1 (Standard Formulation) Dry powder group: 55g metakaolin, 20g negative carbon calcium carbonate, 15g alumina micro powder, 10g quartz powder.
[0034] Liquid group: 12g of anhydrous sodium metasilicate, 1.8g of sodium fluorosilicate (dissolved in 8g of water first), and 35g remaining.
[0035] Glaze slurry composition: 6.5g low-temperature frit powder, 1.8g quartz powder, 1.2g kaolin, 0.2g CMC, 0.05g sodium tripolyphosphate, water. 3.5g.
[0036] Manufacturing process steps: Mix the six dry powder ingredients together for 3 minutes.
[0037] Sodium fluorosilicate is first dissolved in 8g of water, and then the remaining sodium metasilicate is added and stirred well.
[0038] Pour the liquid into the dry powder and mix at low speed for 2-3 minutes until it becomes a thick dough.
[0039] Compact the filling into the silicone mold, vibrate it 15 times to remove air bubbles, and then smooth it out.
[0040] The mold was placed in a 60℃ oven for pre-drying for 24 hours.
[0041] The dry powder of the glaze slurry is passed through a 200-mesh sieve. CMC is dissolved in water and mixed. The mixture is then ball-milled until it passes through a 250-mesh sieve and left to stand for 24 hours.
[0042] The body is sprayed with 3 layers of glaze (total thickness 0.5mm), and each layer is left to air dry for 10 minutes.
[0043] according to Figure 1 Co-firing with heating curve.
[0044] Natural cooling followed by wet polishing with 800-grit sandpaper.
[0045] Results: Initial setting time was 45 minutes, demolding was possible after 24 hours, compressive strength was approximately 38-42 MPa after 7 days, Mohs hardness was 5-6, the glaze was glossy without cracks or bubbles, the cross-section showed no delamination, and the surface felt cool to the touch like ceramic.
[0046] Example 2 (High Carbon Negative Version) The amount of calcium carbonate was increased by 25%, and the amount of metakaolin was reduced to 50%, alumina to 12%, and quartz powder to 13%. The remaining conditions were the same as in Example 1.
[0047] Results: Initial setting time was slightly extended by 60 minutes, 7-day compressive strength was approximately 32-36 MPa (slightly decreased), negative carbon content increased by approximately 20%, shrinkage rate was further reduced, and surface texture was more delicate.
[0048] Comparative Example A (Sodium Fluorosilicate Without Fluorosilicate) Remove sodium fluorosilicate; otherwise, it is the same as in Example 1.
[0049] Results: The hardening time was extended by more than 4 hours, the drying shrinkage was obvious, plastic cracks appeared on the surface, and the 24-hour strength was only about 15 MPa, proving the key role of hardening accelerator in rapid hardening and crack resistance.
[0050] Comparative Example B (no-fired blank directly glazed at 450℃) According to the formula in Example 1, the product is first hardened without firing (cured at room temperature for 7 days), then glazed and fired in a kiln at 450°C.
[0051] Results: Severe blistering of the glaze and cracking of the body surface proved that the "no-fire first, then glaze firing" route is not suitable for the polymer body, and the wet body co-firing route of the present invention must be adopted.
[0052] This invention is based on the alkali-activated condensation polymerization mechanism of geopolymers. Active SiO2 and Al2O3 in metakaolin dissolve under the action of an alkali activator (sodium silicate), forming silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra, which then condense to form an inorganic polymer matrix with a three-dimensional network structure. Sodium fluorosilicate acts as a hardening accelerator, accelerating the formation and hardening of the aluminosilicate gel.
[0053] Calcium carbonate plays a triple role in the system: 1. filling pores and reducing drying shrinkage; 2. improving the rheological properties of the slurry and facilitating molding; 3. serving as an inorganic carbon source to achieve permanent carbon sequestration in the product. Since the maximum co-firing temperature is only 450℃, far below the decomposition temperature of calcium carbonate (approximately 825℃), carbon is sequestered in the matrix in a stable carbonate form, achieving a "negative carbon" function.
[0054] The low-temperature glass glaze is fully vitrified at 450℃, forming a chemical and mechanical bond with the geopolymer body, giving the product ceramic gloss, water resistance, and wear resistance. The wet-fired process allows the body and glaze to shrink synchronously during the heating process, avoiding delamination and cracking.
[0055] In summary, the non-fired negative carbon geopolymer clay and co-firing process provided by this invention eliminate the need for high-temperature sintering above 1000℃ required for traditional ceramics, significantly reducing production energy consumption and carbon emissions. The resulting products possess a ceramic texture and a food-grade surface, making them widely applicable in daily-use ceramics, handicrafts, and building decoration materials. Furthermore, the introduction of calcium carbonate into the formula achieves permanent CO2 carbon sequestration, aligning with the "dual carbon" goal and demonstrating promising industrial application prospects and social benefits.
[0056] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A non-fired negative carbon geopolymer clay, characterized in that, The components include the following parts by weight: 50-60 parts of metakaolin; 15-25 parts of negative carbon calcium carbonate; 10-20 parts of alumina micro powder; 5-15 parts quartz powder; 8-15 parts of anhydrous sodium metasilicate; 1-3 parts sodium fluorosilicate; 30-45 parts water.
2. The non-fired negative carbon geopolymer clay as described in claim 1, characterized in that: The metakaolin has an active Al2O3 and SiO2 content of not less than 70%; the negative carbon calcium carbonate has a CaCO3 content of not less than 90%; the alumina micro powder is α-Al2O3 with a purity of not less than 95%; and the quartz powder has a SiO2 content of not less than 99%.
3. The non-fired negative carbon geopolymer clay as described in claim 1, characterized in that: The modulus of the anhydrous sodium metasilicate is 2.0-3.
3.
4. The non-fired negative carbon geopolymer clay as described in claim 1 or 3, characterized in that: The amount of sodium fluorosilicate used is 12%-15% of the amount of sodium metasilicate with zero water.
5. The non-fired negative carbon geopolymer clay as described in claim 1, characterized in that: The ratio of the amount of water used to the total mass of the non-fired negative carbon polymer clay powder is (0.35-0.40):
1.
6. A low-temperature glass glaze for use in conjunction with the non-fired negative carbon geopolymer clay according to any one of claims 1 to 5, characterized in that, The components include the following parts by weight: Low-temperature frit powder 6-7 parts; Quartz powder 1.5-2 parts; Kaolin 1-1.5 parts; Carboxymethyl cellulose 0.1-0.3 parts; Sodium tripolyphosphate 0.03-0.08 parts; water 3-4 parts.
7. The low-temperature glass glaze used in conjunction with non-fired negative carbon geopolymer clay as described in claim 6, characterized in that: The initial melting point of the low-temperature frit powder is 400-420℃, and it is fully vitrified at 450℃.
8. A method for preparing a product co-fired with non-fired negative carbon geopolymer clay and low-temperature glass glaze, characterized in that, Includes the following steps: Dry powder premix: Mix metakaolin, calcium carbonate, alumina powder and quartz powder in proportion, and dry mix for 2-5 minutes until uniform to obtain a dry powder mixture; Liquid preparation: Sodium fluorosilicate is first dissolved in a portion of water, and then mixed and stirred with the remaining water and anhydrous sodium metasilicate to obtain a mixed liquid; Wet mixing: Pour the liquid mixture into the dry powder mixture and stir for 2-3 minutes until it becomes dough-like to obtain the dough; Compaction molding: The blank is filled into the mold, compacted and vibrated to remove bubbles, to obtain the blank; Low-temperature pre-drying: The green body is pre-dried in an oven at 50-70℃ for 12-24 hours to obtain a semi-dry green body; Glaze preparation: Dry mix low-temperature frit powder, quartz powder and kaolin, then pass through a sieve. Dissolve carboxymethyl cellulose and sodium tripolyphosphate in water and add to the mixture. Stir well and let stand to mature to obtain glaze. Glazing of wet blank: Apply the glaze slurry to the surface of the semi-dry blank, apply 2-3 layers, with a total thickness of 0.4-0.6 mm, and allow each layer to air dry for 10-12 minutes to obtain the glazed blank; Co-firing: The glazed body was co-fired according to the following temperature rise curve: The room temperature was raised to 120℃ at a rate of 1.8–2.2℃ / min, and the temperature was maintained for 15–25 min. Heating from 120℃ to 300℃ at a rate of 0.9–1℃ / min, and holding at that temperature for 30–40 min; Heating from 300℃ to 450℃ at a rate of 1.8–2.2℃ / min, and holding for 10–15 min; The temperature was reduced from 450℃ to 300℃ at a rate of 1.8–2.2℃ / min. Cool down from 300℃ to room temperature and allow to cool naturally.
9. The method for preparing the product co-fired with non-fired negative carbon geopolymer clay and low-temperature glass glaze as described in claim 8, characterized in that: In the co-firing step, the glazed body is co-fired according to the following temperature rise curve: Heat the room temperature to 120℃ at a rate of 2℃ / min and hold for 20min. Heat from 120℃ to 300℃ at a rate of 1℃ / min, and hold for 30–40 min. Heat from 300℃ to 450℃ at a rate of 2℃ / min, and hold for 10–15 min. Cooling from 450℃ to 300℃ at a rate of 2℃ / min; Cool down from 300℃ to room temperature and allow to cool naturally.
10. The method for preparing the product co-fired with the non-fired negative carbon geopolymer clay and low-temperature glass glaze as described in claim 8, characterized in that: In the compaction molding step, the vibration degassing time is 10 to 15 seconds; after co-firing, the product is also wet-polished using 800 to 1500 grit sandpaper and then rinsed with water.